Subcutaneous Immunotherapy Improves the Symptomatology of Allergic Rhinitis - Lourenço,Edmir Américo (2016)
Introduction The relevance of allergic rhinitis is unquestionable. This condition affects people s quality of life and its incidence has increased over the last years. Objective Thus, this study aims to analyze the effectiveness of subcutaneous injectable immunotherapy in cases of nasal itching, sneeze, rhinorrhea and nasal congestion in allergic rhinitis patients. Methods In the present study, the same researcher analyzed the records of 281 patients. Furthermore, the researchers identified allergens through puncture cutaneous tests using standardized extracts containing acari, fungi, pet hair, flower pollen, and feathers. Then, the patients underwent treatment with subcutaneous specific immunotherapy, using four vaccine vials for desensitization, associated with environmental hygiene. The authors analyzed conditions of nasal itching, sneeze, rhinorrhea, and nasal congestion throughout the treatment, and assigned them with a score ranging from zero (0), meaning absence of these symptoms to three (3), for severe cases. The symptoms were statistically compared in the beginning, during, and after treatment. Results In this study, authors analyzed the cases distribution according to age and the evolution of symptomatology according to the scores, comparing all phases of treatment. The average score for the entire population studied was 2.08 before treatment and 0.44 at the end. These results represent an overall improvement of ±79% in symptomatology of allergic rhinitis in the studied population. Conclusion The subcutaneous immunotherapy as treatment of allergic rhinitis led to a reduction in all symptoms studied, improving the quality of life of patients, proving itself as an important therapeutic tool for these pathological conditions.